Method for preparing isodecene by catalyzing isoamylene dimerization through solid acid
By loading zirconium sulfate tetrahydrate on mesoporous molecular sieve to form a solid acid catalyst, the shortcomings of liquid acid catalysts in the prior art in the oligomerization reaction are solved, and the efficient catalysis and product selectivity of isoprene dipolymerization into isodene is achieved, and there is good industrial application prospect.
Patent Information
- Application Number
- CN202411824696.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, liquid acid catalysts have problems such as poor product selectivity, difficulty in separation, waste liquid pollution in light olefin oligomerization reaction, which limits the industrial application of the oligomerization process.
By dispersing zirconium sulfate tetrahydrate onto a mesoporous molecular sieve with a high specific surface area, a supported solid acid catalyst is formed, and the pore structure of the molecular sieve is used to improve the catalytic efficiency.
It has achieved efficient catalysis of isoprene dipolymerization into isodene, with high product selectivity, easy separation of catalyst and product, and has environmentally friendly industrial application prospects.
Smart Images

Figure CN119569520A_ABST
Abstract
Description
Technical Field
[0001] The invention provides a method for preparing isodecene by dimerization of isopentene catalyzed by solid acid, belonging to the field of preparing high-value oil products by oligomerization of light olefins. Background Art
[0002] With the development of petrochemical industry, the production capacity of ethylene produced from liquid hydrocarbons is growing. The cracking C5 fraction is the main by-product of the ethylene plant, so C5 resources are becoming more and more abundant. The current research focus is on the utilization of diolefins in the C5 fraction, including isoprene, isoprene, dicyclopentadiene, etc., because they are ideal raw materials for synthesizing polymers. However, in addition to diolefins, there are quite a lot of monoolefins in the C5 fraction, including 1-pentene, 2-pentene, 2-methyl-1-butene, 2-methyl-2-butene, 3-methyl-1-butene, etc. The current utilization rate of them is generally low. It is a pity to burn them as fuel, and they should be considered for conversion and utilization. Due to the volatility and high activity of isopentene, they are one of the "culprits" of tropospheric ozone, accounting for more than 90% of gasoline ozone formation. The ozone in the troposphere is one of the components of photochemical smog and is a pollutant harmful to organisms. Converting light olefins into high-value products (such as gasoline, diesel, lubricants and other fine chemical raw materials) through oligomerization is an effective way to improve their utilization. Isodecene, which is produced by dimerization of isopentene, has a very high octane number of 96. The octane number of isodecane produced by hydrogenation is 105, so it can be used as an alternative to petroleum additives. Isodecene can also be used to synthesize surfactants, manufacture lubricants, plasticizers and other petrochemical products. In addition, industrial or edible flavors can be made through reactions such as epoxidation and acylation. Therefore, the generation of isodecene by dimerization of isopentene can not only reduce pollutants in gasoline components, but also convert it into high-value products, bringing both environmental and economic benefits.
[0003] The polymerization of light olefins is a typical acid-catalyzed reaction, and its efficient polymerization depends on the design and use of the catalyst. Early polymerization processes usually use liquid acid catalysts such as sulfuric acid, hydrofluoric acid, and toluenesulfonic acid, but such liquid acid catalysts have obvious shortcomings, such as poor product selectivity, difficult separation, waste liquid pollution, and equipment corrosion, which seriously limit the industrial application of the polymerization process. In order to further improve the catalytic polymerization process, researchers have developed a variety of new solid acid catalysts and applied them to the polymerization of light olefins. Such as solid phosphoric acid catalysts, acidic ion exchange resin catalysts, acidic ionic liquid catalysts, supported sulfate catalysts, and molecular sieve catalysts. Phosphoric acid catalysts have low mechanical strength, are easy to muddy and agglomerate, and corrode equipment; ionic liquids are complex to prepare and expensive; sulfonic acid resin catalysts, although they are highly acidic, have a wide distribution of polymerization products, including dimerization, trimerization, and even tetramerization products; and microporous molecular sieves are medium-strong acids with relatively weak acidity, and the reaction conversion rate and rate are low. At present, there are few studies on the dimerization of isopentene to prepare isodecen. Patent CN202210420616.9 discloses a three-dimensional phenyl framework organic porous catalyst and patent CN202110294169.2 discloses a mesoporous SiO2-loaded heteropolyacid catalyst for the reaction of isopentene dimerization to prepare isodecen. However, the catalyst preparation method used in the above two patents is complicated, the processing process is cumbersome, and there is a problem of high raw material cost. Therefore, developing a cheap, efficient and environmentally friendly catalyst is the key to the dimerization of isopentene. The catalyst provided by the present invention has a cheap and easy-to-obtain synthetic raw material, a simple preparation method, does not need to undergo processes such as high energy consumption roasting, and has a good performance in catalyzing the dimerization of isopentene. Summary of the invention
[0004] The purpose of the present invention is to provide a method for catalyzing the dimerization of isopentene into isodecene using a solid acid catalyst with a simple preparation process and being environmentally friendly. Zirconium sulfate tetrahydrate is a layered compound and a sulfate solid acid with strong acidity. However, due to its small specific surface area, the effective utilization rate of the active center when used alone as a catalyst is very low. The present invention disperses zirconium sulfate tetrahydrate on a mesoporous molecular sieve with a high specific surface area to form a more evenly distributed active center, and utilizes the shape-selective effect of the highly ordered pore structure of the molecular sieve to achieve the purpose of catalyzing the dimerization of isopentene into isodecene with high efficiency. To achieve the above purpose, the present invention adopts the following technical scheme: The method for solid acid catalyzed isopentene dimerization to isodecenes is characterized in that zirconium sulfate supported on a mesoporous carrier is used as a solid acid catalyst, isopentene is used as a reactant, and the reaction is stirred at 50-90° C. for 1-10 hours under a nitrogen pressure of 0.5-5 MPa. The mass ratio of isopentene to catalyst is 10:1-80:1.
[0005] The catalyst preparation method is to load zirconium sulfate with acidic sites onto a mesoporous carrier by an equal volume impregnation method, that is, zirconium sulfate tetrahydrate is dissolved in deionized water, and then the catalyst carrier is slowly added, fully stirred and mixed at room temperature, and then allowed to stand for aging for 10-12 hours, and then the water is dried under reduced pressure to obtain a loaded solid acid catalyst.
[0006] The catalyst carrier is one of MCM-41, MCM-48, SBA-15 and mesoporous silica gel.
[0007] The loading amount of zirconium sulfate in the catalyst is 10%-50% of the carrier mass.
[0008] During the catalyst preparation process, the temperature is 100-120° C., the pressure is 100-1000 Pa, and the rotary evaporation drying is performed for 3-5 hours.
[0009] Compared with the traditional preparation method, the present invention has the following advantages: the raw materials for preparing the catalyst in the catalytic system are cheap and readily available, the preparation method is simple, no high energy consumption process such as roasting is required, and no additional solvent is required in the reaction process. The present invention utilizes the strong acidic site of zirconium sulfate to make it uniformly dispersed on the carrier to form more active centers, and utilizes the shape-selective effect of the carrier pores to make it show very high selectivity for isopentene dimer. At the same time, the catalyst and the product are easy to separate, the environment is friendly, and there is a good prospect for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is the gas chromatogram of isopentene dimerization to isodecen according to Example 1 of the present invention.
[0011] FIG2 is a mass spectrogram of different isomers of isodecene synthesized in various embodiments of the present invention, wherein af is the mass spectrograms of the products synthesized in embodiments one, two, four, six, seven, and eight, respectively. DETAILED DESCRIPTION
[0012] The present invention is further explained below with reference to specific embodiments.
[0013] The isopentene raw material used in the present invention is a mixture of 2-methyl-2-butene (90%) and 2-methyl-1-butene (10%). The product analysis in each embodiment adopts Agilent Technologies 6820 gas chromatography system for quantitative analysis. The chromatographic conditions are: chromatographic column 30 m × 0.25 mm × 0.33 μm capillary, hydrogen flame ionization (FID) detector. Qualitative analysis is completed using Agilent Technologies 7890B-5977A GC-MS, and the chromatographic conditions are: chromatographic column 30 m × 0.25mm × 0.25 μm capillary, EI ion source, long-term high-energy electron multiplier detector.
[0014] Embodiment 1 1.0 g of zirconium sulfate tetrahydrate was dissolved in 12 ml of deionized water, and then 2.0 g of MCM-41 catalyst carrier was slowly added. After being fully stirred and mixed at room temperature, the mixture was allowed to stand for 12 hours, and then the water was removed by rotary evaporation at a temperature of 120° C. and a pressure of 150 Pa for 5 hours to obtain a MCM-41-supported zirconium sulfate solid acid catalyst.
[0015] 0.1 g of the solid acid catalyst and 3.0 g of isopentene were weighed and placed in a 90 ml stainless steel autoclave, filled with 2.0 MPa nitrogen, and reacted at 70° C. for 3 h. After the reaction, the temperature of the autoclave was lowered to 5° C., the gas in the autoclave was discharged, the solid catalyst was separated by a high-speed centrifuge, and the product was analyzed by gas chromatography. The conversion rate of isopentene was 70%, and the selectivity of isodecenes was 96%.
[0016] Embodiment 2 0.7 g of zirconium sulfate tetrahydrate was dissolved in 12 ml of deionized water, and then 2.0 g of MCM-41 catalyst carrier was slowly added. After being fully stirred and mixed at room temperature, the mixture was allowed to stand for 12 h. Then, the water was removed by rotary evaporation at a temperature of 110 ° C and a pressure of 120 Pa for 5 h to obtain a MCM-41-supported zirconium sulfate solid acid catalyst.
[0017] 0.1 g of the solid acid catalyst and 3.0 g of isopentene were weighed and placed in a 90 ml stainless steel autoclave, filled with 2.0 MPa nitrogen, and reacted at 70° C. for 5 h. After the reaction, the temperature of the autoclave was lowered to 5° C., the gas in the autoclave was discharged, the solid catalyst was separated by a high-speed centrifuge, and the product was analyzed by gas chromatography. The conversion rate of isopentene was 62%, and the selectivity of isodecenes was 97%.
[0018] Embodiment 3 0.5 g of zirconium sulfate tetrahydrate was dissolved in 12 ml of deionized water, and then 2.0 g of MCM-41 catalyst carrier was slowly added. After being fully stirred and mixed at room temperature, the mixture was allowed to stand for 12 h. Then, the water was removed by rotary evaporation at 120 ° C. and 160 Pa. A solid acid catalyst of zirconium sulfate supported on MCM-41 was obtained.
[0019] 0.1 g of the solid acid catalyst and 3.0 g of isopentene were weighed and placed in a 90 ml stainless steel autoclave, filled with 2.0 MPa nitrogen, and reacted at 70° C. for 5 h. After the reaction, the temperature of the autoclave was lowered to 5° C., the gas in the autoclave was discharged, the solid catalyst was separated by a high-speed centrifuge, and the product was analyzed by gas chromatography. The conversion rate of isopentene was 54%, and the selectivity of isodecenes was 97%.
[0020] Embodiment 4 0.2 g of zirconium sulfate tetrahydrate was dissolved in 12 ml of deionized water, and then 2.0 g of MCM-41 catalyst carrier was slowly added. After being fully stirred and mixed at room temperature, the mixture was allowed to stand for 12 hours, and then the water was removed by rotary evaporation at a temperature of 120° C. and a pressure of 200 Pa for 5 hours to obtain a MCM-41-supported zirconium sulfate solid acid catalyst.
[0021] 0.1 g of the solid acid catalyst and 3.0 g of isopentene were weighed and placed in a 90 ml stainless steel autoclave, filled with 2.0 MPa nitrogen, and reacted at 70° C. for 5 h. After the reaction, the temperature of the autoclave was lowered to 5° C., the gas in the autoclave was discharged, the solid catalyst was separated by a high-speed centrifuge, and the product was analyzed by gas chromatography. The conversion rate of isopentene was 31%, and the selectivity of isodecenes was 98%.
[0022] It can be seen from Examples 1 to 4 that, with the increase in the loading of zirconium sulfate, the acidic centers thereof gradually increase, and the isopentene conversion rate also increases accordingly, but the selectivity of the dimer isodecenes decreases slightly.
[0023] Embodiment 5 0.5 g of zirconium sulfate tetrahydrate was dissolved in 5 ml of deionized water, and then 1.0 g of SBA-15 catalyst carrier was slowly added. After being fully stirred and mixed at room temperature, the mixture was allowed to stand for 10 h. Then, the mixture was dried by rotary evaporation at a temperature of 110° C. and a pressure of 150 Pa for 5 h to remove moisture, thereby obtaining a SBA-15-loaded zirconium sulfate solid acid catalyst.
[0024] 0.1 g of the solid acid catalyst and 3.0 g of isopentene were weighed and placed in a 90 ml stainless steel autoclave, filled with 2.0 MPa nitrogen, and reacted at 70° C. for 5 h. After the reaction, the temperature of the autoclave was lowered to 5° C., the gas in the autoclave was discharged, the solid catalyst was separated by a high-speed centrifuge, and the product was analyzed by gas chromatography. The conversion rate of isopentene was 60%, and the selectivity of isodecenes was 94%.
[0025] Embodiment 6 0.35 g of zirconium sulfate tetrahydrate was dissolved in 5 ml of deionized water, and then 1.0 g of SBA-15 catalyst carrier was slowly added. After being fully stirred and mixed at room temperature, the mixture was allowed to stand for 10 hours, and then the water was removed by rotary evaporation at a temperature of 120°C and a pressure of 200 Pa for 3 hours to obtain a SBA-15-loaded zirconium sulfate solid acid catalyst.
[0026] 0.1 g of the solid acid catalyst and 3.0 g of isopentene were weighed and placed in a 90 ml stainless steel autoclave, filled with 2.0 MPa nitrogen, and reacted at 70° C. for 5 h. After the reaction, the temperature of the autoclave was lowered to 5° C., the gas in the autoclave was discharged, the solid catalyst was separated by a high-speed centrifuge, and the product was analyzed by gas chromatography. The conversion rate of isopentene was 55%, and the selectivity of isodecenes was 96%.
[0027] Embodiment 7 Dissolve 0.5 g of zirconium sulfate tetrahydrate in 5 ml of deionized water, then slowly add 1.0 g of a commercial mesoporous SiO2 carrier, fully stir and mix at room temperature, let stand for 12 hours, and then rotary evaporate and dry for 5 hours at a temperature of 120°C and a pressure of 200 Pa to obtain a mesoporous SiO2-loaded zirconium sulfate solid catalyst.
[0028] 0.1 g of the solid acid catalyst and 3.0 g of isopentene were weighed and placed in a 90 ml stainless steel autoclave, filled with 2.0 MPa nitrogen, and reacted at 70° C. for 5 h. After the reaction, the temperature of the autoclave was lowered to 5° C., the gas in the autoclave was discharged, the solid catalyst was separated by a high-speed centrifuge, and the product was analyzed by gas chromatography. The conversion rate of isopentene was 68%, and the selectivity of isodecenes was 88%.
[0029] Embodiment 8 The catalyst preparation process is the same as in Example 1.
[0030] 0.05 g of the solid acid catalyst and 3.0 g of isopentene were weighed and placed in a 90 ml stainless steel autoclave, filled with 2.0 MPa nitrogen, and reacted at 70° C. for 5 h. After the reaction, the temperature of the autoclave was lowered to 5° C., the gas in the autoclave was discharged, the solid catalyst was separated by a high-speed centrifuge, and the product was analyzed by gas chromatography. The conversion rate of isopentene was 33%, and the selectivity of isodecenes was 98%.
[0031] Embodiment 9 The catalyst preparation process is the same as in Example 1.
[0032] 0.2 g of the solid acid catalyst and 3.0 g of isopentene were weighed and placed in a 90 ml stainless steel autoclave, filled with 2.0 MPa nitrogen, and reacted at 70° C. for 5 h. After the reaction, the temperature of the autoclave was lowered to 5° C., the gas in the autoclave was discharged, the solid catalyst was separated by a high-speed centrifuge, and the product was analyzed by gas chromatography. The conversion rate of isopentene was 78%, and the selectivity of isodecenes was 90%.
[0033] From Examples 8 and 9, it is shown that the amount of catalyst used has a significant effect on the conversion rate of isopentene and the selectivity of isodecane. When the amount of catalyst used is 0.1 g, the conversion rate of isopentene is low. When the amount of catalyst used is 0.2 g, although the conversion rate is slightly increased, the selectivity of isodecane is also significantly reduced.
[0034] Comparative Example 1 0.1 g of zirconium sulfate tetrahydrate and 3.00 g of isopentene were weighed and placed in a 90 ml stainless steel autoclave, filled with 2.0 MPa nitrogen, and reacted at 70°C for 5 hours. After the reaction, the autoclave temperature was lowered to room temperature, the gas in the autoclave was discharged, the solid catalyst was separated by a high-speed centrifuge, and the product was analyzed by gas chromatography. The conversion rate of isopentene was 10%, and the selectivity of isodecenes was 88%.
[0035] Comparative Example 2 Weigh 0.1g of MCM-41 molecular sieve and 3.00g of isopentene into a 90ml stainless steel autoclave, fill with 2.0MPa nitrogen, and react at 70°C for 5h. After the reaction, cool the autoclave to room temperature, exhaust the gas in the autoclave, separate the solid catalyst using a high-speed centrifuge, and analyze the product using gas chromatography. The conversion rate of isopentene is 5%, and the selectivity of isodecen is 97%.
[0036] Comparative Example 3 Weigh 0.1g of Amberlyst-15 sulfonic acid resin and 3.00g of isopentene into a 90ml stainless steel autoclave, fill with 2.0MPa nitrogen, and react at 70°C for 5h; after the reaction, cool the autoclave to room temperature, discharge the gas in the autoclave, separate the solid catalyst using a high-speed centrifuge, and analyze the product using gas chromatography. The conversion rate of isopentene is 83%, the selectivity of isodecenes is 75%, and there are many cracking products with boiling points close to isodecenes that are difficult to separate.
[0037] Comparative Example 4 0.1g of beta molecular sieve (silicon-aluminum ratio of 60) and 3.00g of isopentene were weighed and placed in a 90ml stainless steel autoclave, filled with 2.0MPa nitrogen, and reacted at 70°C for 5h; after the reaction, the reactor temperature was lowered to room temperature, the gas in the reactor was discharged, the solid catalyst was separated by a high-speed centrifuge, and the product was analyzed by gas chromatography. The conversion rate of isopentene was 42%, and the selectivity of isodecenes was 95%.
[0038] It can be seen from the examples and comparative examples that the activity of simple zirconium sulfate tetrahydrate and carrier MCM-41 is very low. When zirconium sulfate tetrahydrate is loaded on MCM-41 to form a solid acid catalyst, its catalytic performance is significantly improved. Compared with sulfonic acid resins and catalyst molecular sieves, the catalyst of the present invention has a higher isodecene yield, and there is no obvious cracking product in the product, which is conducive to the separation of the isodecene product later.
Claims
1. A method for synthesizing isodecene by dimerization of isopentene catalyzed by solid acid, characterized in that: The method uses zirconium sulfate supported on a mesoporous carrier as a solid acid catalyst, uses isopentene as a reactant, and reacts at 50-90°C under a nitrogen pressure of 0.5-5MPa for 1-10 hours under stirring. The preparation method of the solid acid catalyst is as follows: zirconium sulfate with acidic sites is loaded onto a mesoporous carrier by an equal volume impregnation method, that is, zirconium sulfate tetrahydrate is dissolved in deionized water, and then slowly added into the mesoporous carrier, and after being fully stirred and mixed at room temperature, the mixture is allowed to stand for 10-12 hours, and then the water is removed by decompression and spin drying to obtain a loaded solid acid catalyst.
2. The method for preparing isodecene by solid acid catalyzed isopentene dimerization according to claim 1, characterized in that: The mesoporous carrier is one of MCM-41, MCM-48, SBA-15 and mesoporous silica gel.
3. The method for preparing isodecene by solid acid catalyzed isopentene dimerization according to claim 1, characterized in that: The loading amount of zirconium sulfate in the catalyst is 10%-50% of the carrier mass.
4. The method for preparing isodecene by solid acid catalyzed isopentene dimerization according to claim 1, characterized in that: During the catalyst preparation process, the temperature is 100-120° C., the pressure is 100-1000 Pa, and the rotary evaporation is performed for 3-5 hours.
5. The method for preparing isodecene by solid acid catalyzed isopentene dimerization according to claim 1, characterized in that: The mass ratio of isopentene to catalyst used is 10:1 to 80:1.
Citation Information
Patent Citations
Method for preparing isodecanene by catalytic dimerization of isopentenene
CN113024336B
Three-dimensional phenyl framework organic porous catalyst for catalyzing isopentenene dimerization
CN114870895B